Evaluasi Sistem Keuangan Desa dengan Technology Acceptance Model - Rhosalina Damayanti; Putu Prema Sulistyaning Putri; Aprina Nugrahesthy Sulistya Hapsari (Jurnal Akuntansi, 2022)
The purpose of this research is to evaluate the implementation of Siskeudes in the management of village fundsby using the Technology Acceptance Model (TAM) approach in Gedangan Village. Data acquired by in-depth observation and interviews with village officers and operators of Siskeudes and will be explained using a qualitative descriptive method. The result of this research show that the use of Siskeudes as a media for managing village funds in Gedangan Village are useful, easy to use and also shorten the time for preparing the reports. However, the use of Siskeudes in Gedangan Village is still not optimal due to the limitation of the human resources either in quantity or the ability to mastering technology. The benefit of this research is to enrich the literature for further research and provide recommendations for the government to re-formulate a strategy to improve the quality of village officers to operate the Siskeudes. The conclusion obtained from this researh are Siskeudes facilitate (perceived of ease of use) and useful (perceived of usefulness) in managing village funds. It is also able to help the government in turning a crisis of public trust into an opportunity for more accountable and transparance in managing bugdet. Keywords: Village Funds, Perceived of Ease of Use, and Perceived of Usefulness